FRI0077 Hepatitis b virus reactivation in patients with rheumatoid arthritis treated with baricitinib: post-hoc analysis from clinical trials. (12th June 2018) - Harigai, M.; Winthrop, K.; Takeuchi, T.; Hsieh, T.-Y.; Chen, Y.-M.; Smolen, J.S.; Burmester, G.R.; Walls, C.; Wu, W.-S.; Dickson, C.; Liao, R.; Genovese, M.C.
Abstract : Background: Baricitinib (BARI) is an oral selective Janus kinase (JAK)1 and JAK2 inhibitor approved in the EU, Japan, and other countries for treatment of moderately to severely active rheumatoid arthritis (RA) in adults. RA therapies may increase risk of hepatitis B virus (HBV) infection 1 . HBV reactivation is a concern in previously infected patients (pts), including those with serologic evidence of resolution. HBV exposure is common in many Asian countries. 2 Limited data exist on HBV reactivation among pts with RA treated with JAK inhibitors. Objectives: To assess HBV reactivation in pts with RA treated with BARI during Phase (Ph) 3 trials. Methods: At screening, all pts were tested for HBV surface antigen (HBsAg), core antibody (HBcAb) and surface antibody (HBsAb). In Japan and elsewhere if required, pts had screening HBV DNA tests. Pts were excluded if they had 1) HBsAg+, 2) HBcAb+/HBsAb- (in Japan, could enrol if HBV DNA-), or 3) HBsAb +and HBV DNA+. Routine HBV DNA monitoring was performed in Japan for pts with HBcAb +and/or HBsAb +at screening, and was later instituted globally for HBcAb +pts. Pts with post-baseline HBV DNA+ (≥29 IU/mL) were discontinued from the study and referred to a hepatologist. In select cases, investigators continued study drug following a HBV DNA +test in consultation with the sponsor and in accordance with HBV management guidelines. Data were integrated from 4 completed Ph 3 trials and 1 ongoing long-term extension (LTE) (data to April 2017). Results: Of 2890 pts with ≥1 dose of BARI (6993 pt-years exposure), 269 pts had baseline serology suggestive of prior infection (HBcAb+/HBsAb+, n=255; HBcAb+/HBsAb-, n=14) (figure 1). Post-baseline HBV DNA tests were performed for 290 pts (including some pts without a baseline HBV DNA result). After BARI initiation, 7 of 201 pts (3%) with HBcAb+/HBsAb +at baseline had quantifiable HBV DNA +levels (≥29 IU/mL; median 256, range 31–1547 IU/mL). An additional 23 (11%) had qualitative HBV DNA +results below the lower limit of detection (LLD)(<29 IU/mL). Of these 30 HBcAb+/HBsAb +pts with HBV DNA +tests post-baseline, 22 had HBV DNA- tests at baseline. Among 14 pts with HBcAB+/HBsAb-, all had HBV DNA- tests at baseline; repeat HBV DNA test results post-baseline were quantifiable (1 at 36 IU/mL), below the LLD, 1 and undetectable. 12 Of pts with quantifiable HBV DNA, adverse events (AE) of detectable HBV DNA resulted in discontinuation of 4 of 8 pts of whom 3 received antivirals. 4 of 8 pts continued BARI in the LTE and have not received antivirals. All pts with quantifiable HBV DNA had alanine transaminase (ALT) or aspartate transaminase (AST) within normal limits, and none had an investigator-reported AE of hepatitis. Conclusions: Approximately 12% of BARI-treated pts with prior HBV infection later tested HBV DNA+ (3% were above the LLD), although no pts developed clinical evidence of hepatitis and in most cases antiviral therapy was not used. References: [1] Chen MH, et al. J Infect Dis2017;215(4):566–73. [2] Chen YM, et al. JMII 2017. Disclosure of Interest: M. Harigai Grant/research support from: BristolMyers Squibb K.K., Eisai Co., Ltd., Ono Pharmaceuticals, and Takeda Pharmaceutical Co., Ltd, Consultant for: Eli Lilly and Company, K. Winthrop Grant/research support from: Pfizer, BMS, Consultant for: Pfizer, UCB, Abbvie, Eli Lilly and Company, Amgen, BMS, T. Takeuchi: None declared, T.-Y. Hsieh: None declared, Y.-M. Chen: None declared, J. Smolen Grant/research support from: AbbVie, Janssen, Eli Lilly and Company, MSD, Pfizer, Roche, Consultant for: AbbVie, Amgen, Astra-Zeneca, Astro, BMS, Celgene, Celltrion, Chugai, Gilead Glaxo, ILTOO, Janssen, Eli Lilly and Company, Medimmune, MSD, Novartis-Sandoz, Pfizer, Roche, Samsung, Sanofi-Aventis, UCB, G. Burmester Consultant for: Eli Lilly and Company, C. Walls Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, W.-S. Wu Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, C. Dickson Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, R. Liao Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, M. Genovese Grant/research support from: Eli Lilly and Company, AbbVie, Consultant for: Eli Lilly and Company, AbbVie,